Novel Biopolymer Matrices for Microencapsulation of Phages: Enhanced Protection Against Acidity and Protease Activity - Dini, Cecilia (2012)
Phage therapy by oral administration as a strategy to reduce enterohemorrhagic E. coli from cattle requires enhanced resistance of phage to the harsh gastric conditions (extreme acidity and protease activities). The purpose of this work is the microencapsulation of phage in non-toxic and natural biopolymeric matrices as a protective barrier against gastric environment. Alginate and pectin are used as base polymers. Further emulsification with oleic acid or coating with a different biopolymer is also under study. Emulsified pectin gel micropsheres showed the maximum encapsulation efficiency and the highest protection against acidity, leaving more than 103 active phages after 30 min. exposure at pH 1.6, and allowing a full retention of phage titre after 3h incubation with pepsin (4.2 mg ml-1). Full inactivation of non-encapsulated phage at pH 1.6 or with 0.5 mg ml-1 pepsin after 10 min. incubation was found. The results obtained in vitro strongly suggest that emulsified gel pectin matrix may significantly increase phage resistance to the gastric system for oral delivery.